Study on a novel field-measured load calibration method for the life assessment of the metro bogie frame. (June 2022) - Zhang, Zifan; Ru, Changle; Li, Qiang
Highlights: A time–frequency method is proposed for multi-channel load calibration. Based on the quasi-static relationship between load and stress as well as the multiaxial spectral method, the expression of stress statistics in the frequency domain is derived considering the correlation of multiple loads. According to the damage consistency principle, the NSGA-II multi-objective optimization algorithm is used to calibrate the load system. Abstract: Aiming at solving the problem of premature fatigue failure of the bogie frame of a metro vehicle during service, this paper mainly studies the method of accurately predicting the fatigue life of the bogie frame of a metro train through the measured load. To correct the error between the calculated damage and real damage value, a hybrid frequency-time calibration method is proposed. Based on the quasi-static relationship between the load and stress as well as the basic theory of the multiaxial spectral method, the expression of stress statistics in the frequency domain is derived considering the correlation of multiple loads. According to the damage consistency principle, the NSGA-II multi-objective optimization algorithm is used to calibrate the load system. Based on the frequency domain calibration results, the dynamic stress time history could be acquired by the Inverse Fast Fourier Transform (IFFT) method. The results show that the calculated damage through the calibrated load completely covers the real damage value, and the ratio range between them is 1.10–1.42. The above results indicate that the calibrated load can be used for the reliability design of later structural optimization.